A microglial kinase ITK mediating neuroinflammation and behavioral deficits in traumatic brain injury - Afridi, Ruqayya; Bhusal, Anup; Lee, Seung Eun; Hwang, Eun Mi; Ryu, Hoon; Kim, Jong-Heon; Suk, Kyoungho (Academic Press, 2025)
Microglia-mediated neuroinflammation has been implicated in the neuropathology of traumatic brain injuries (TBI). Recently, the expression of interleukin-2-inducible T-cell kinase (ITK) has been detected in brain microglia, regulating their inflammatory activities. However, the role of microglial ITK in TBI has not been investigated. In this study, we demonstrate that ITK expression and activation are upregulated in microglia following an injury caused by controlled cortical impact (CCI) - a mouse model of TBI. Pharmacological inhibition of ITK protein or knockdown of microglial ITK gene expression using adeno-associated virus mitigates neuroinflammation and improves neurological outcomes in the CCI model. Additionally, ITK mRNA expression was found to be increased in the brains of patients with chronic traumatic encephalopathy. An ITK inhibitor reduced the activation of inflammatory responses in both human and mouse microglia in vitro. Collectively, these results suggest that microglial ITK plays a pivotal role in neuroinflammation and mediating behavioral deficits following TBI. Thus, targeting the signaling pathway of microglial ITK may exert protective effects by alleviating neuroinflammation associated with TBI.